Knowing what you want - why disembodied repentance is impossible - Rooney, James Dominic (Religious studies, 2025)
It is a reasonable worry that God would not truly love us and want our salvation if He fixed a definite point after which He will no longer offer us the graces to repent of our sins. I propose that Thomas Aquinas succeeds in showing us that God would not be cruel or arbitrary in setting up a world where embodied agents end up after death in a state where they will inevitably fail to repent of their sins. Aquinas proposes that being disembodied is to be in a state where a person cannot be mistaken about what they want, given that they know themselves perfectly. If the disembodied state were like this, it would not be surprising that being in that state makes repentance impossible, since a soul would become fully integrated around whatever one desired, without any conflicting desires that could prompt repentance. Thus, humans would persist in whatever desires they had at the moment of death and disembodiment. I conclude by arguing that, while this scenario stands in need of fuller theodicy, Aquinas’s scenario is helpful in defending a view that God is not cruel or arbitrary for creating a world in which post-mortem repentance is impossible.